Human Behavior in Social Context - Annisa Rahma; Wantini Wantini (Jurnal Impresi Indonesia, 2024)
Humans are complex social beings, and their behavior is influenced by interactions with their social environment. In this context, a deep understanding of the factors that shape human behavior is essential. This research aims to understand how cultural values, norms, and traditions influence human behavior in a particular social context. This research uses the case study method. Research subjects may include diverse groups of people involved in social interactions, such as individuals from different age groups, cultures, and socio-economic backgrounds. Data collection techniques include participant observation and case studies. The results show that human behavior in social contexts is strongly influenced by various factors, including culture, norms, and interactions between individuals. Data analysis confirmed that culture plays an important role in shaping behavior, with cultural values influencing individual decisions and actions.